Efektivitas Pijat Refleksi Kaki Terhadap Kontrol Glikemik dan Neuropati Perifer Pada Pasien Diabetes Melitus: A Systematic Literature Review - Shindy Gustarina; Rini Damayanti; Sudirman Sudirman (Universitas Pahlawan Tuanku Tambusai, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by persistent hyperglycemia and a risk of complications such as peripheral neuropathy and lower extremity circulatory disorders. Foot reflexology is widely used as a non-pharmacological complementary therapy in the management of DM, but existing research results still show variation. Therefore, a synthesis of scientific evidence is needed to comprehensively assess the effectiveness of this intervention. The method used was a systematic literature review by analyzing 19 national and international journal articles with randomized controlled trials (RCTs), quasi-experimental, case studies, and systematic reviews. The outcome variables studied included blood glucose levels, HbA1c, peripheral neuropathy, ankle brachial index (ABI), neuropathic pain, and patient comfort. The analysis was conducted by comparing results before and after the intervention and between the intervention and control groups. The results showed that most studies showed a significant decrease in blood glucose and HbA1c levels after foot reflexology. Improvements were also found in peripheral neuropathy symptoms, including reduced pain and increased foot sensitivity. Studies with RCT designs provided stronger evidence, although there was heterogeneity in the duration and frequency of intervention. Foot reflexology massage has the potential to be a safe and effective complementary therapy to support glycemic control and improve peripheral neuropathy in patients with diabetes. However, studies with more robust methodological designs and standardized intervention protocols are needed to support the implementation of evidence-based practices.